The medico-legal investigation of death in custody - a review of cases admitted to the Pretoria Medico-Legal Laboratory, 2007-2011 - Du Toit-Prinsloo, Lorraine (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2013.